The Effect of Corporate Social Responsibility and Company Size on Company Value - Alya Trinandya Rosha Bun Yani; Radhi Abdul Halim (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2023)
Every company will of course continue to develop and implement business benefits built to grow corporate value. Added corporate value can be implemented through CSR along with company size. The purpose of this research is to find out the impact of Corporate Social Responsibility (CSR) and company size on company value. All mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period were included in this research. In this study the sample was determined using a purposive sampling technique so that a sample of 19 companies was found. The data analysis technique applies panel data, while the processing uses Eviews 12.0. This research proves that CSR does not affect company value. Furthermore, the size of the company also does not affect the value of the company.